Craps games / Mohd Arrey Mohd Ghazali and Ahmad Salehim Abdullah - Mohd Ghazali, Mohd Arrey (2004)
Craps games are one of the projects that we are be able to designed and make it such as the electronic games. Here we suppose to do list up what we need about these games. This game function is so easy. Actually this electronic games use 12 LED that the LED is such as the output for this games function. These Craps games only use battery supply about 9V. For the circuit it just uses two digital IC 4017 and 4093. This game circuit is a simple integrated circuit. This circuit can be used to provide LED output such as a light in the parallel array. For the children these games can be one interactive game. It also can give entertainment to them. For the children, this games very easy to handle. It because, we designed this games with two switches. This project consists of several devices such as resistors, capacitors, two-decade counters, switches and a display LED parallel with a 12 segment LED display. Pressing switches 1 and 2 should start the operation of circuit game. These switches are to connecting with two-decade counter. On the other hand, lead 15 operates as a reset. A 9 V battery power supplies to the lead 16 in the both Digital’s IC. To start with fresh game, first we supplied 9V and then press either switches 1 or 2. After that, the LED shows the display. If want to start it one again, press reset at the lead 15. The main objective of this circuit game is to analyze the operation of decade counter, quad two input Schmitt trigger and twelve LED displays